Republic Act No. 7716. IN Document Section [column] (Philippine Journal of Public Administration, 1994)
An act restructuring the value-added tax (vat) system, widening its tax base and enhancing its administration, and for these purposes amending and repealing the relevant provisions of the national internal revenue' code, as amended, and for other purposes.